2022
DOI: 10.3390/ijms232315239
|View full text |Cite
|
Sign up to set email alerts
|

Tear Proteomics Approach to Distinguishing Primary from Secondary Sjögren’s Syndrome for Dry Eye Patients with Long-Term Instillation of Eyedrops

Abstract: The diagnosis and monitoring of Sjögren syndrome (SS) is often difficult, requiring a multidisciplinary approach with invasive procedures. Our aim is to elucidate the tear protein alterations of dry eye disease (DED) with primary SS (pSS) and secondary SS (sSS) with the long-term instillation of eyedrops. We collected clinical demographics and tear fluid (TF) samples from DED patients with no autoimmune diseases (non-SS-DED), pSS-DED, and sSS-DED patients, followed by TF screening with tandem mass tagging-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Another potential candidate biomarker for SS diagnosis is A Desintegrin and Metalloproteinase domain-containing protein 10 (ADAM10). In a 2022 study, ADAM10 was found for the first time to be significantly increased in SS patients compared to non-SS patients [72].…”
Section: Tear Analysis 431 Tear Proteomicsmentioning
confidence: 95%
See 1 more Smart Citation
“…Another potential candidate biomarker for SS diagnosis is A Desintegrin and Metalloproteinase domain-containing protein 10 (ADAM10). In a 2022 study, ADAM10 was found for the first time to be significantly increased in SS patients compared to non-SS patients [72].…”
Section: Tear Analysis 431 Tear Proteomicsmentioning
confidence: 95%
“…Tear proteomic analysis has gained popularity as a diagnostic method for SS via biomarker investigation, as tears can be collected in a non-invasive manner, allowing for easy identification of ocular surface biomarkers [72].…”
Section: Tear Analysis 431 Tear Proteomicsmentioning
confidence: 99%
“…The masked technicians interpreted the examination procedure for the subject before each tear film test. After completing a dry eye questionnaire with Ocular Surface Disease Index (OSDI) [24], each subject received a series of ocular surface examinations with the K5M, including TMH [25][26][27][28][29], TFV [15,16,30,31], ocular surface redness [26,28,29,32], NIKBUT [25][26][27][28][29], and meibography [27,28,33]. Finally, each subject received cobalt blue light illuminated corneal photography after fluorescence dye staining to determine the corneal epitheliopathy [28,29,34].…”
Section: Assessment Protocolmentioning
confidence: 99%
“…Over the past 15 years, a few reports have involved the analysis of tear proteins in SS-DED patients using untargeted LC-MS approaches for their identification and relative quantitation. , From these studies, many potential disease biomarkers have been proposed based on the analysis of one cohort of patients. The screening and diagnosis of SS remain challenging, and the etiology of the disease is still not well established.…”
Section: Introductionmentioning
confidence: 99%